2021
DOI: 10.1161/strokeaha.120.032867
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cerebral Artery Stroke: Role of Collateral Systems on Infarct Topography

Abstract: Background and Purpose: The circle of Willis (CoW) and leptomeningeal anastomoses play an important role in transforming infarct topography following middle cerebral artery occlusion. Their role in infarct topography following anterior cerebral artery occlusion is not well understood. The aim of this study was to evaluate the role of the CoW and leptomeningeal anastomoses in modifying regional variation in infarct topography following occlusion of the anterior cerebral artery and its branches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
(88 reference statements)
0
15
0
Order By: Relevance
“…The MCA perfused various brain regions, including subcortical regions (e.g., corona radiata, internal capsule, globus pallidus, caudate nucleus, thalamus) and the cerebral cortex (e.g., primary motor cortex and premotor cortex). [33][34][35][36] According to fMRI studies, subcortical infarction in the corona radiata and internal capsule is confirmed following MCA territory infarction. [37][38][39] Given that the CST and CFT axons project to the corona radiata and internal capsule, 34,35 we thought that degeneration of the CST and CFT could be attributed to damage in the subcortical white matter by MCA territory infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The MCA perfused various brain regions, including subcortical regions (e.g., corona radiata, internal capsule, globus pallidus, caudate nucleus, thalamus) and the cerebral cortex (e.g., primary motor cortex and premotor cortex). [33][34][35][36] According to fMRI studies, subcortical infarction in the corona radiata and internal capsule is confirmed following MCA territory infarction. [37][38][39] Given that the CST and CFT axons project to the corona radiata and internal capsule, 34,35 we thought that degeneration of the CST and CFT could be attributed to damage in the subcortical white matter by MCA territory infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of an infarct in the paracentral lobule in our study was low (0.05) which would lead us to conclude that the paracentral lobule is less likely to be involved in motor deficit (see Table 1). The low probability of infarction of the paracentral lobule can be explained by the compensatory capacity of leptomeningeal anastomoses which exist between cortical branches of the ACA (posterior inferior frontal, paracentral, and superior parietal arteries) and MCA (central, precentral, and anterior parietal arteries) [7].…”
Section: Impact Of Changing Perfusion Deficit On Involvement By Corti...mentioning
confidence: 99%
“…The M1, premotor cortices, and SMA are supplied by branches of the middle cerebral artery (MCA) and anterior cerebral artery (ACA). Following vessel occlusion, the compensatory capacity of collateral systems, the Circle of Willis, and interterritorial leptomeningeal anastomoses will attempt to maintain cerebral perfusion and, in the process, modify infarct topography [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As a major neurological disease, ischemic stroke is mainly caused by atherosclerosis, cardiac embolism, and cerebral small-vessel occlusion ( 1 ). Cerebral artery occlusion can cause cerebral ischemia and hypoxia, leading to neuronal apoptosis and brain parenchyma necrosis ( 2 ). These pathological changes may lead to neurological dysfunction, disability, or even death.…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal apoptosis after ischemic stroke has been widely studied to salvage dysfunctional neurons ( 2 ). Generally, apoptosis caused by stroke is mediated through numerous pathways, such as the mitochondrial pathway and the protein 53 (p53)-mediated apoptosis pathway ( 4 ).…”
Section: Introductionmentioning
confidence: 99%